Application of bromide-iodide lead perovskite thin film as a copper-free back contact layer for CdTe solar cells. (December 2021) - Zhou, Biao; Zhang, Fan; Zhang, Junlin; Yang, Xiutao; Li, Kelin; Zeng, Guanggen; Li, Bing; Zhang, Jingquan; Zhao, Dewei; Constantinou, Iordania; Hao, Xia; Karazhanov, Smagul; et al.
Graphical abstract: Highlights: CH3 NH3 Pb(I1-x Brx )3 perovskite thin films are successfully applied as copper-free back contact layers for CdTe solar cells. The facile deposition process of back contact layers. The uniformity of CdTe solar cell is improved after applying CH3 NH3 Pb(I1-x Brx )3 back contact layers. CdTe solar cell with a CH3 NH3 Pb(I1-x Brx )3 back contact layer exhibits good stability. Abstract: In this study, bromide-iodide lead perovskite (CH3 NH3 Pb(I1−x Brx )3 ) thin films were fabricated and applied as copper-free back contact layers for CdTe solar cells. The results reveal that the open-circuit voltage (Voc ) and fill factor (FF) of the CdTe solar cells are greatly enhanced by the utilization of perovskite back contact layers. This is mainly due to the evidently reduced charge transportation barrier at the back contact, which is verified by temperature-dependent current–voltage (J-V-T) and apparent quantum efficiency (AQE) measurements. Specifically, after the application of perovskite back contact layer, the best-performing device shows 15.80% improvement in efficiency (from 10.82 to 12.53%), with Voc and FF increasing by 3.94% and 6.91%, respectively. Besides, the overall uniformity of the solar cells is also improved by the perovskite back contact, suggested by laser beam induced current (LBIC) results. Further simulation results confirm the experimental results and clarify the optimized cell performance by perovskite back contact layer in terms of both energy band alignment and charge carriers' recombination. In addition, in the simulation section, we have also investigated the effect of the bandgap, thickness and doping level of perovskite and the doping level of CdTe on the cell performances. The experiments and the numerical simulation reported in this work suggest perovskite a potential copper-free back contact layer for the fabrication of efficient CdTe solar cells.